1989
DOI: 10.1016/0022-510x(89)90031-2
|View full text |Cite
|
Sign up to set email alerts
|

A light and electron microscopical study of B-50 (GAP-43) in human intramuscular nerve and neuromuscular junctions during development

Abstract: The growth associated protein B-50 (GAP-43) is demonstrated in human intramuscular nerves and neuromuscular junctions by light microscopy and electron microscopy. Nearly all fetal endplates are shown to be immunoreactive for B-50. The percentage of B-50 positive endplates decreases significantly during the peri- and neonatal period, but in children and adults a low percentage of B-50 positive endplates remains present. These data indicate that also in the human peripheral nervous system the expression of B-50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

1992
1992
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
3
7
1
Order By: Relevance
“…These authors reported that a decrease in the number of B-50-positive end plates is observed with the age of the individuals, indicating that also in human peripheral nervous system the B-50 expression is developmentally regulated. In corroboration of the findings of Hesselmans et al (1989), we show that the NM4 Mabs detect very well outgrowing axons in developing peripheral human nervous tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These authors reported that a decrease in the number of B-50-positive end plates is observed with the age of the individuals, indicating that also in human peripheral nervous system the B-50 expression is developmentally regulated. In corroboration of the findings of Hesselmans et al (1989), we show that the NM4 Mabs detect very well outgrowing axons in developing peripheral human nervous tissue.…”
Section: Discussionsupporting
confidence: 89%
“…This suggestion is supported by recent observations of Masliah et al ( 199 1 ) . Hesselmans et al (1989), using a polyclonal rabbit antibody to B-50, showed by light and electron immunomicroscopy that B-50 is present in intramuscular nerve fibers and at motor end plates of human muscle biopsies. These authors reported that a decrease in the number of B-50-positive end plates is observed with the age of the individuals, indicating that also in human peripheral nervous system the B-50 expression is developmentally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at previous literature concerning expression of B-50 in muscle tissue, it seems that our findings contrast with the results of Hesselmans et al in 1989 [13]. In developing muscle they found B-50 in human intramuscular nerves and neuromuscular junctions, but not in myocytes.…”
Section: Discussioncontrasting
confidence: 99%
“…Spanish Phartnucwigdance Syjtem (Cantabrian Regional 2) and in regenerated nerve terminals [I, 31. Parhad and colleagues C41 recently reported that GAP-43 messenger RNA expression is increased two to four times in the anterior horn cells of the spinal cord of patients with amyotrophic lateral sclerosis (ALS).…”
Section: Clinical Pharmacology Unitmentioning
confidence: 99%
“…Although CNS adverse reactions have been reported after use of terfenadine products in adults 111, in controlled clinical studies, no significant difference between terfenadine and placebo in the incidence of these effects was found [2]. The lack of significant terfenadine penetration into the central nervous system (CNS) is probably responsible for its lack of CNS effects.…”
mentioning
confidence: 99%